2017
DOI: 10.1136/bmjopen-2016-015616
|View full text |Cite
|
Sign up to set email alerts
|

National audit of pressure ulcers and incontinence-associated dermatitis in hospitals across Wales: a cross-sectional study

Abstract: ObjectiveThe Chief Nurse National Health Service Wales initiated a national survey of acute and community hospital patients in Wales to identify the prevalence of pressure ulcers and incontinence-associated dermatitis.MethodsTeams of two nurses working independently assessed the skin of each inpatient who consented to having their skin observed.ResultsOver 28 September 2015 to 2nd October 2015, 8365 patients were assessed across 66 hospitals with 748 (8.9%) found to have pressure ulcers. Not all patients had t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 13 publications
2
28
0
Order By: Relevance
“…Although most PIs in the general population are considered preventable when correct prevention strategies are implemented, PIs in palliative care patients may be unavoidable as a result of skin failure . PI is a common hospital‐acquired complication in the Western world and has been linked to poor adherence to prevention strategies across clinical settings . Although there are various barriers to clinical practice guideline implementation, Australian and international studies have reported that nurses' knowledge of PI prevention strategies is often inadequate.…”
Section: Introductionmentioning
confidence: 99%
“…Although most PIs in the general population are considered preventable when correct prevention strategies are implemented, PIs in palliative care patients may be unavoidable as a result of skin failure . PI is a common hospital‐acquired complication in the Western world and has been linked to poor adherence to prevention strategies across clinical settings . Although there are various barriers to clinical practice guideline implementation, Australian and international studies have reported that nurses' knowledge of PI prevention strategies is often inadequate.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in The United Kingdom, it is estimated that the value of the registered annual costs varies from 1,4 to 2,1 milliard pounds, representing 4% of the total costs for medical assistance in The United Kingdom [6], and in Spain, pressure-ulcer treatment required approximately 5% of the total costs for medical care [7]. Pressure-ulcer prevalence registers high values and varies from a country to country as follows: in Jordan,12%, Norway, 54%, Ireland, 16%, Denmark, 15%, Sweden, 25%, Wales 8,9% [4,[8][9][10][11][12].…”
Section: The Importance Of the Topicmentioning
confidence: 99%
“…In the paediatric acute care setting, one study reported a skin tear prevalence of 17% (McLane et al, 2004). A recent audit of in-patients in acute hospitals across Wales identified a prevalence of 2.57% (Clark et al, 2017).…”
Section: Prevalence Of Skin Tearsmentioning
confidence: 99%